2019
DOI: 10.1186/s13048-019-0498-0
|View full text |Cite
|
Sign up to set email alerts
|

Tomm34 is commonly expressed in epithelial ovarian cancer and associates with tumour type and high FIGO stage

Abstract: Background: Increased activity of the chaperones Hsp70 and Hsp90 is a common feature of solid tumours. Translocase of the outer mitochondrial membrane 34 (Tomm34) is a cochaperone of both Hsp70 and Hsp90 that was found to be overexpressed in colorectal, hepatocellular, lung and breast carcinomas. The expression profile of Tomm34 in ovarian cancer has not been investigated. Therefore, the aim of the current study was to investigate the expression pattern of Tomm34 in ovarian carcinomas and analyse its correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…TOMM34 is a protein located in the outer membrane of mitochondria (TOMM), which plays a role in importing preprotein into the mitochondria ( 58 ). A previous study found that TOMM34 was overexpressed in colon cancer ( 59 ), ovarian cancer ( 60 ), and breast cancer ( 61 ) and served as a biomarker of the progression and poor prognosis of ovarian and breast cancer. However, to date, the role of ACOT7, ADPRHL2, ATAD3A, FAM72A, PDSS1, RAD51C, and TOMM34 in HCC almost unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TOMM34 is a protein located in the outer membrane of mitochondria (TOMM), which plays a role in importing preprotein into the mitochondria ( 58 ). A previous study found that TOMM34 was overexpressed in colon cancer ( 59 ), ovarian cancer ( 60 ), and breast cancer ( 61 ) and served as a biomarker of the progression and poor prognosis of ovarian and breast cancer. However, to date, the role of ACOT7, ADPRHL2, ATAD3A, FAM72A, PDSS1, RAD51C, and TOMM34 in HCC almost unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Located in the cytoplasm, TOMM34 is known to interact with HSP70 and HSP90 and regulate the activity of ATPase ( 55 ). High expression of TOMM34 has been found in colon cancer ( 56 ), breast cancer ( 57 ), and ovarian cancer ( 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…As we known, TP53 mutation is a famous carcinogenetic factor of OSCC, which leads to the instability of the tumor genome [ 37 ]. Tomm34 expression levels indicates poor prognosis for p53-mutant epithelial ovarian cancer [ 20 ]. Our bioinformatic analysis indicated that higher expression of Tomm34 was detected in TP53-mutant OSCC compared with TP53-nonmutant OSCC and normal tissue ( p < 0.001) ( Supplementary Figure S1 ), and further research will be required to elucidate the regulation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Tomm34 can interact with Hsp70 and Hsp90 to form Hsp70-Tomm34-Hsp90 complex, which acts as a co-chaperon of Hsp70 and Hsp90 to regulate its function [ 13 , 14 ]. Recent studies showed high levels of Tomm34 expressed in colorectal cancer [ 15 ], hepatocellular carcinoma [ 16 ], bladder cancer [ 17 ], breast cancer [ 18 , 19 ] epithelial ovarian cancer [ 20 ] and colon cancer [ 21 ] compared to their normal tissue counterparts. However, the expression of Tomm34 in oral squamous cell carcinoma primary tumor has not been reported and its role in OSCC is still unclear.…”
Section: Introductionmentioning
confidence: 99%